2016
DOI: 10.1038/srep29912
|View full text |Cite
|
Sign up to set email alerts
|

Differences in gray matter structure correlated to nationalism and patriotism

Abstract: Nationalism and patriotism both entail positive evaluations of one’s nation. However, the former inherently involves derogation of other nations, whereas the latter is independent of comparisons with other nations. We used voxel-based morphometry and psychological measures and determined nationalism and patriotism’s association with gray matter density (rGMD) and their cognitive nature in healthy individuals (433 men and 344 women; age, 20.7 ± 1.9 years) using whole-brain multiple regression analyses and post … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
(99 reference statements)
0
3
1
2
Order By: Relevance
“…Interestingly, family income was associated with greater nationalism and competitive achievement motivation, which is a third novel finding. The reason for this association is not clear; however, we have previously shown greater nationalism is associated with a feeling of superiority to others (Takeuchi et al, 2016b), and the data in the present sample also showed a positive correlation between competitive achievement motivation and a feeling of superiority to others. This kind of feeling caused by greater family income may lead to nationalism and competitive achievement motivation.…”
Section: Discussioncontrasting
confidence: 62%
“…Interestingly, family income was associated with greater nationalism and competitive achievement motivation, which is a third novel finding. The reason for this association is not clear; however, we have previously shown greater nationalism is associated with a feeling of superiority to others (Takeuchi et al, 2016b), and the data in the present sample also showed a positive correlation between competitive achievement motivation and a feeling of superiority to others. This kind of feeling caused by greater family income may lead to nationalism and competitive achievement motivation.…”
Section: Discussioncontrasting
confidence: 62%
“…We regarded state anxiety and GSES as partly overlapping, a neural basis that could not be regressed. Accordingly, as we explained previously (Takeuchi et al 2016b ), we did not regard state anxiety as a confounding variable.…”
Section: Methodsmentioning
confidence: 99%
“…For analyses of ASL measurements using each individual's non‐normalized segmented gray matter map and white matter map, which were produced from the segmentation process, an artificial image was created for each individual from the function of ‘1 × gray matter map + 2 × WM map’. The contrast of this artificial ‘1 × gray matter map + 2 × white matter map’ was similar to that of the R1 map of ASL (as confirmed by visual inspection) and was used in the following preprocessing of ASL images.…”
Section: Methodsmentioning
confidence: 99%